Investigation into the use of millimeter wavelengths electromagnetic radiation for remote control of water solutions properties - Лошицкий, П.П.; Минзяк, Д.Ю. (Radiotekhnika, 2012)
The action of extremely low-intensity electromagnetic radiation modulated with a hydrogen peroxide solution on the microorganisms life is investigated. The possibility to change properties of electromagnetic wave interaction with a matter for remote estimation of concentration and control of aqueous solutions properties is shown.